The Marginalized Maqasid al-Shariah Problems of Profit Orientation in Indonesia's Islamic Financial System - Arum, Hafidza Sanshia; Andrini, Rozi (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This study addresses the growing concern over the marginalization of maqasid al-shariah the ethical and social objectives of Islamic law in Indonesia’s Islamic financial institutions (IFIs). Despite notable growth in assets and institutional presence, many IFIs remain fixated on profit-maximization, often replicating conventional banking models and neglecting the core values of Islamic economics such as justice, welfare, and human dignity. Methods: This research employs a qualitative-descriptive approach using a normative-philosophical method. Data were collected through document and content analysis of Islamic financial regulations, fatwas, academic publications, and policy papers. The study also applies triangulation to enhance data validity and reliability.. Results: Findings indicate that profit orientation dominates Islamic banking operations in Indonesia, with little institutional incentive to implement maqasid-aligned policies. Regulatory indicators such as ROA and CAR fail to reflect social objectives, and maqasid literacy among practitioners remains low. These gaps have contributed to reduced social impact, especially among lower-income groups who are central to maqasid values. Conclusion and suggestion: The study recommends the integration of a Maqasid Shariah Index (MSI) into regulatory evaluation tools, development of socially-oriented products such as qard hasan and productive waqf, and mandatory maqasid education for IFI leadership. These steps aim to create a more balanced, ethical, and socially inclusive Islamic financial ecosystem in Indonesia.